Low neonatal blood glucose levels in cesarean-delivered term newborns at Khartoum Hospital, Sudan - Hussein, Shahad M (BioMed Central, 2014)
ABSTRACT: BACKGROUND: Glucose is the main source of energy for organ function in neonates. There are few published recent data on neonatal glucose levels during cesarean delivery. METHODS: A case (cesarean delivery) -control (vaginal delivery) study was conducted at Khartoum Hospital Sudan to compare blood glucose levels of term newborns born after elective cesarean delivery with those born vaginally. RESULTS: Cord blood glucose levels at delivery were significantly lower in women who had a cesarean delivery compared with those who delivered vaginally (99.8 ± 20.6 vs. 106.8 ± 11.1 mg/dl, P = 0.026), but there was no significant difference (97.8 ± 16.7 vs. 102.1 ± 9.6, P = 0.110) in newborn glucose levels at 2 hours after delivery between the groups. In linear regression, cesarean delivery (-6.475 mg/dl, P = 0.013) and maternal blood glucose levels at the time of delivery (+0.619 mg, P < 0.001) were significantly associated with mean cord glucose levels. CONCLUSION: This study shows that cord blood glucose levels are significantly lower in cesarean-delivered neonates than vaginally-delivered neonates. In addition, cord blood glucose levels are significantly associated with cesarean delivery and maternal blood glucose levels at delivery. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2011479878124993